Impact of the Social Demonstrance of Luxury Brands on Brand Engagement Behaviors: Role of Consumer-brand Identification - Wyne, Mariam Abuzar; Khan, Faheem Ahmad; Shafi, Khurram (International Review of Management and Marketing, 2018)
Drastic dynamism in internet technology and the evolution of social media has had a major impact on the way firms interact and build relationships with their customers online. Social networking sites (SNSs) such as Facebook, allow firms to interact directly with their customers through online brand communities (OBCs). This study draws from the social impact, social identity and social exchange theory to explore social demonstrance as an external and consumer brand identification as an internal force that influences brand engagement on OBCs. The study looks into the impact of the social importance of luxury brands specifically and the extent to which consumers personally identify with the brand on specific brand engagement behaviors; operationalized as participation and promotion based on the behavioral aspect of brand engagement. An online questionnaire was administered to the fans of particular fashion designer clothing brand pages on Facebook and data was gathered from 332 respondents. The empirical findings of the study concluded that consumers choose to identify more with luxury brands that are socially dominant in order to enhance their social image among others. Therefore luxury brand marketers must focus on developing a strong brand personality that matches the identity of target customers. Keywords: Social demonstrance, Brand engagement Behavior through Online Brand Communities (OBCs), Consumer brand identification. JEL Classification: M1